PEMBELAJARAN FISIKA DENGAN METODE TUTOR SEBAYA UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI DITINJAU DARI GAYA BELAJAR SISWA - sakti, oki purwa; Jumini, Sri; Khoiri, Ahmad (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2022)
The purpose of this study was to determine the significance of the relationship between: Is the peer tutoring method learning in terms of student learning styles able to improve students' communication skills This research was conducted at MTs Takhassus Al-Qur'an Wonosobo, academic year 2022/2023 with a population of 185 students divided into 5 classes. Samples were taken by random sampling, as research samples were class VII D, which consisted of 33 students and class VII E, which consisted of 31 students. Retrieval of data using a questionnaire technique. The test results are in the form of student learning outcomes, while the questionnaire technique is in the form of a questionnaire score of student learning styles and communication skills using observation. Hypothesis analysis used a two-way ANOVA test, from the first hypothesis it was found that Hoa was accepted F count 0.317 ≤ F table 3.15 so that the use of the peer tutoring method had no effect on communication skills. As for the results of the second hypothesis from the calculation, the result is that Fcount is 4.507 ≤ 4.00, then the Hob is rejected, this shows that there is an influence of student learning styles (visual, auditory and kinesthetic) on communication skills. Furthermore, the results of the third hypothesis are used to test the interaction between the peer tutoring method and student learning styles, the Hoab value is accepted, meaning that there is no interaction between the peer tutoring method and student learning styles with an F count of 3.105 ≤ F table 3.15 To find out more about the differences between the three problems above, a marginal mean table was calculated using the peer tutor method row a1 (peer tutor method) and row a2 (conventional). The mean of peer tutoring method learning in terms of student learning styles is 65,625 While the average student learning outcomes using conventional methods is 56. The implication of this research is that learning Physics using peer tutoring methods in terms of student learning styles can overcome difficulties in student learning so that it can affect student learning outcomes.